How to Appraise a Clinical Trial Critically. (1st December 1995) - Sutherland, Lloyd R
Abstract : Most clinicians wish to base their therapeutic decisions on scientific data but are often overwhelmed by the number of case reports, open series and other therapeutic trials published each year. It is essential to develop a personal screening plan that can alert the clinician to which reports deserve extra attention, as they may alter management, and to which reports can be ignored. The first step is to review the abstract. Decisions related to therapeutics should be based on 'randomized', 'controlled', 'double-blinded', 'clinical trials'. If these key words are not included in the abstract, it is unlikely that the report will change clinical practice. Each of these terms describes an essential element that attempts to assure that the results of the trial will be unbiased and generally applicable to clinical practice. The next step is to examine the 'Methods' section. Clinicians should be interested in the inclusion and exclusion criteria. Two questions arise. First, do the study participants resemble patients in your practice? Second, how many patients were assessed in order to enrol the study population? If only a few of the patients screened actually entered the trial the results may not be of use for the general population with the disease. Another important screening process is to review the 'Statistical' section. It is not necessary to be a statistician, but one should read the section to determine whether a sample size calculation was performed and whether confidence intervals have been calculated around the major end-points. By remembering these key concepts, clinicians can reduce the number of journal articles they read without compromising their ability to be informed of major breakthroughs in the management of disease.